PEMETAAN KEARIFAN LOKAL BUDAYA SASI LAUT DI NEGERI NUWEWANG KECAMATAN PULAU LETTI, KABUPATEN MALUKU BARAT DAYA - Rakuasa, Heinrich; Pinoa, W S (Jurnal Geografi, 2023)
Local wisdom is an effort and community resilience to manage and preserve their natural products based on certain customary rules. Since the 16th century, natural resources in Maluku have been managed by a system called sasi. Sasi as a form of communal resource management practice carried out for generations in various locations in Maluku and parts of West Papua, this practice has long been believed to be one of the traditional wisdoms that are efficient in preserving natural resources. This study focuses more on mapping the marine sasi area in Nuwewang Country, sea sasi itself is a traditional open and close system for the use of certain marine resources that applies from generation to generation. This study aims to map local wisdom in the form of sea sasi which is applied in the State of Nuwewang. The methods used are surveys and interviews, with data analysis carried out spatially using remote sensing methods based on geographic information systems. The results showed that the sea sasi boundary from the east starts from Tanjung Ayam to Tanjung Garam in the west with a coastline length of 13.34 Km. The total area of Sasi Laut in Nuwewang Country is 514.12 Ha.